Finding a treatment that fits : a grounded theory of adolescent retention in alcohol and drug treatment : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts in Psychology at Massey University - McKenzie, Heather Lianne (Massey University, 2008)
The present study sought to uncover the process youth go through and the factors that influence the decision to dropout of drug and alcohol treatment. The study reports the experiences of 9 participants from a residential therapeutic community treatment programme in Auckland. Participants' ages ranged fron 14 to 17 years. The study utilised a qualitative approach, specifically, a grounded theory approach. Treatment dropout was found to be a complex process that was specific to the individual. A range of client, programme, and other factors were found to influence participants' decisions to dropout of the treatment programme. Recommendations are included for clinicians and suggestions for future research are made.
Keywords: Substance abuse treatment; Teenagers; Therapeutic communities' evaluation